Embracing Immersive Journalism: Adoption and Integration by News Media Producers - Ioanna Georgia Eskiadi; Nikolaos Panagiotou (Journalism and Media, 2024)
Immersive journalism, utilizing virtual reality (VR) and augmented reality (AR) technologies, offers a transformative approach to storytelling by creating deeply engaging news experiences. This study examines the acceptance of immersive journalism by people working in news media industries focusing on different demographic groups. Using qualitative focus groups, participants from varied age groups experienced VR news stories and discussed their perceptions and responses. Key findings revealed high emotional engagement across all demographics, with younger participants showing greater enthusiasm and ease with the technology, while older participants expressed interest but faced technological barriers. Trust in the media and perceived realism were crucial factors influencing acceptance. Concerns about accessibility and inclusivity were also significant, particularly among older and less technologically proficient participants. This study concludes that, for immersive journalism to gain widespread acceptance, media organizations must address technological barriers, enhance user education, and ensure ethical standards in storytelling. These insights contribute to understanding how immersive journalism can be integrated into mainstream media to enhance audience engagement and trust, highlighting the importance of accessibility and emotional resonance in the adoption of innovative media technologies.